Dynamic Response Simulation of Lining Structure for Tunnel Portal Section under Seismic Load - Guoqing Liu; Juntao Chen; Ming Xiao; Yang Yang (Shock and Vibration)
Portal section is the weak link of seismic fortification for tunnel structure. Assuming that seismic wave is the vertical incident elastic plane wave, the plane wave input method for the portal section was discussed in this paper; that is, the wave input problem can be converted to the problem of calculating equivalent nodal force at artificial boundaries. Based on different damage evolution processes of concrete under tension and compression conditions, the tension and compression damage variables were defined and solved, respectively. And then a simple elastic dynamic damaged constitutive model for concrete lining was built. According to the characteristics of dynamic interaction between the lining and rock, and based on the dynamic contact force algorithm, an analytical model for joint loading between the lining and rock was built. This model can simulate lining features such as bond, separation, and slip under seismic load. The dynamic response characteristics of lining structure for the portal section under seismic load were analyzed by taking example for an exit section of Dianzhong diversion project in strong earthquake area. The results show that the relative displacement magnitudes of the lining parts are related to the vibration direction of the seismic wave, and the peak displacements decrease gradually to the fixed values from the portal to the interior. The damage coefficients of the lining parts accumulate gradually over time, and the farther the lining is away from the portal, the less serious the seismic damage is. The separation and slip zone distributions of the lining are basically consistent with its severe seismic damage area, which are mainly at haunch, spandrel, and arch foot within a certain range of distance from the portal. The seismic fortified length and key fortified parts of tunnel structure for the portal section can be determined according to the calculation results.